Model Learning Cycle 7E Terhadap Keterampilan Berpikir Spasial dan Hasil Belajar Siswa - M. Rizqon Al Musafiri; Bejo Aprianto; Chalia Chistella (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Critical and spatial thinking skills are urgently needed in 21st-century education, especially in Geography. This study aims to investigate the influence of the Learning Cycle 7E model on students' learning outcomes and spatial thinking skills. The research method used is a quasi-experimental design with pre-tests and post-tests where data were analyzed using ANOVA to determine the significance of differences between groups. The results show that implementing the Learning Cycle 7E model significantly improves students' understanding, indicated by an increase in average post-test compared to pre-test scores and a more evenly distributed range of high-category scores. Students' spatial thinking skills also improved, with reduced variation among students after the learning intervention. The ANOVA test yielded an F-value of 5.436 with a significance of 0.033 (p < 0.05) indicating a significant difference between groups. The between-group Sum of Squares was 118.778, and the between-group Mean Square was 8.484, higher than within groups (Mean Square = 5.908), reinforcing significant differences. This study emphasizes the importance of cycle-based learning approaches like the Learning Cycle 7E to optimize learning outcomes and develop students' critical and spatial thinking skills.